A Grammar of Modern Standard Balochi - Jahani, Carina (Studia Iranica Upsaliensia, 2019)
Balochi is an Iranian language spoken in Pakistan, Iran, Afghanistan, the Gulf States (particularly Oman and the United Arab Emirates), Turkmenistan, India, and East Africa. Informal estimates suggest that no less than 10 million people speak the language. It can be divided into three main dialect blocks, Western, Southern and Eastern Balochi. Ever since the mid-20th century, there have been attempts to create a unified orthography for Balochi. The development of written Balochi has mainly taken place in Pakistan, where there have been advocates of both the Arabic and Latin scripts. Most literature, of course, has been written in Arabic script, but even here diverging systems have been used. In 2012, at the initiative of Uppsala University, the University of Balochistan and the Balochi Academy, Quetta, as well as a number of Baloch authors and literary societies, a programme was launched with the purpose of working towards the standardization of Balochi orthography and grammar. At an orthography conference held in Uppsala in 2014, the participants decided to work on two parallel orthographies, one based on the Arabic script and one on the Latin script. In 2016, a grammar conference was held, at which some of the areas of grammatical variation in Balochi were discussed and suggestions were made about what forms to include in the standard written Balochi language. In order to create and promote a standard Balochi language, it is important to include as many intellectuals as possible in the process, in order to gain a consensus for the suggested standard language. This description of Modern Standard Balochi orthography, phonology, morphology, syntax and word-formation is based on discussions held at the conferences and on further input from a number of renowned Baloch writers and linguists.